Estructura organizacional en la gestion administrativa de las pymes agricolas en el Cantón Buena Fe Provincia de Los Ríos, 2015. - Chévez Fuentes, Karen Valeria (2016)
This research aims to design an organizational structure in the Administrative Management of Agricultural SMEs in the canton Buena Fe, Los Rios Province. To improve its structure. This research began applying a survey as data collection technique, to thereby identify the current situation of agricultural SMEs. Thus we obtain accurate information and see to meet the objectives of the proposal, the results of this research showed us the lack of knowledge in the administration by the managers of SMEs are not being managed as companies, they do not carry out directional basis or properly established organizational structure, these parameters do not have specific grounds or as values, policies, mission and vision; because this empiricism is shown which are carrying out the work and it is for this reason that there are shortcomings and problems in SMEs. It is for this reason we do this research with the aim of putting as guides administrators and encourage good development and growth of SMEs in the canton different Buena Fe.